Quality of Life Philosophy IV. The Brain and Consciousness - Søren Ventegodt; Niels Jørgen Andersen; Joav Merrick (The Scientific World Journal)
In this article we look at the brain’s structure and function from a philosophical perspective. Although the brain at micro-level, with its trillions of ultra-thin nerve fibers, is one of the most complicated structures in the known universe, you can still grasp its composition if you go up to the level of the cell. How this structure functions is not quite clear. You can understand its function at fiber level, because it is fairly simple, and you can understand it at cell level, but it is already vague. Roughly speaking, you can envision a single nerve cell as a tiny, independent computer whose behavior is dependent on continuous calculations of all input. At organ level, the function can be understood as an extremely complex pattern machine. Finally, the brain’s function can be understood at the cognitive level as what provides consciousness through its ability to keep order in our complicated reality. The superior function of the brain is to connect the real us, our higher self, to the surrounding world.The brain has been developed so that it can create all possible complex patterns. The connectivity seems to imply that the patterns of the human brain are 1000-dimensional. It is our vision that these complicated patterns arise from basic patterns in the quantum matter of which everything is created. In our opinion, our consciousness’ special utilization of a patterned aspect of nature is what lies behind inscrutable statements like “Man is created in God’s image”. We suggest that these patterns in matter are the basic, creative force that influences all living organisms. Unfortunately, science has only just begun to understand these patterns.The Bible’s description of the origin of man is two people eating from the Tree of Knowledge and as punishment they are expelled from the Garden of Eden. What does that mean? It means that, as conscious creatures, we no longer were an unproblematic, harmonious part of the world around us. The great question is why this consciousness about the world, provided by the brain, is not a gift that makes life better instead of getting us expelled from the Garden of Eden. We think that our real problem is the fact that we are still not in control of our consciousness. Instead of it serving us, we have become its slaves. If we come to understand brain and consciousness in order to solve this basic problem of our existence, we shall again be able to become a coherent part of the world, both as individuals and as a species. We share the vision that such an understanding of the problems of consciousness will make medical science holistic and will bring quality of life, health, and the ability to function to its patients.